2017
DOI: 10.1177/2333794x17696683
|View full text |Cite
|
Sign up to set email alerts
|

Less Invasive Surfactant Administration Reduces the Need for Mechanical Ventilation in Preterm Infants

Abstract: Neonatal respiratory distress syndrome due to surfactant deficiency is associated with high morbidity and mortality in preterm infants, and the use of less invasive surfactant administration (LISA) has been increasingly studied. This meta-analysis found that LISA via thin catheter significantly reduced the need for mechanical ventilation within the first 72 hours (relative risk [RR] = 0.677; P = .021), duration of mechanical ventilation (difference in means [MD] = −39.302 hours; P < .001), duration of suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 32 publications
6
40
0
3
Order By: Relevance
“…Kribs et al were the first to portray a strategy to administer surfactant via a thin tube using Magill forceps. Use of such a method has been shown to reduce the need for mechanical ventilation (MV) in a few of the trials . However, the evidence is not robust and the results are equivocal.…”
Section: Introductionsupporting
confidence: 85%
See 4 more Smart Citations
“…Kribs et al were the first to portray a strategy to administer surfactant via a thin tube using Magill forceps. Use of such a method has been shown to reduce the need for mechanical ventilation (MV) in a few of the trials . However, the evidence is not robust and the results are equivocal.…”
Section: Introductionsupporting
confidence: 85%
“…Transient bradycardia and desaturation were observed only in SurE group among 19 (11%) patients. The observed complication rate in the present study population is less than the previously reported rates . This may be explained due to higher gestation of our study population (31 vs 28 weeks) compared to the previous trial and prior training of the doctors involved in the administration of surfactant.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations